2022
DOI: 10.3389/fped.2022.812781
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Fetal Fraction in Noninvasive Prenatal Screening: A Review

Abstract: A paradigm shift in noninvasive prenatal screening has been made with the discovery of cell-free fetal DNA in maternal plasma. Noninvasive prenatal screening is primarily used to screen for fetal aneuploidies, and has been used globally. Fetal fraction, an important parameter in the analysis of noninvasive prenatal screening results, is the proportion of fetal cell-free DNA present in the total maternal plasma cell-free DNA. It combines biological factors and bioinformatics algorithms to interpret noninvasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 131 publications
5
18
0
Order By: Relevance
“…The mean of fetal fractions was also calculated for the four groups and classified according to BMI: 13.2% (±3.62) in the underweight group (BMI < 18.5), 12.1% (±3.39) in the healthy group (18.5–25), 9.99% (±3.10) in the overweight group (25–30), and 8.91% (±2.67) in the obese group (≥30) ( Figure 1 B). Contrary to the gestational age, fetal fraction tended to decrease as BMI increased ( p < 0.05 for all pairwise comparisons); therefore, our study confirmed that BMI and period of pregnancy can affect the fetal fraction [ 22 ].…”
Section: Resultssupporting
confidence: 76%
“…The mean of fetal fractions was also calculated for the four groups and classified according to BMI: 13.2% (±3.62) in the underweight group (BMI < 18.5), 12.1% (±3.39) in the healthy group (18.5–25), 9.99% (±3.10) in the overweight group (25–30), and 8.91% (±2.67) in the obese group (≥30) ( Figure 1 B). Contrary to the gestational age, fetal fraction tended to decrease as BMI increased ( p < 0.05 for all pairwise comparisons); therefore, our study confirmed that BMI and period of pregnancy can affect the fetal fraction [ 22 ].…”
Section: Resultssupporting
confidence: 76%
“…We found statistically significant differences between the two groups regarding maternal BMI, gestational age at delivery, and method of delivery. This is not surprising given that associations of fetal fraction with gestational age and maternal BMI are well established in previous publications [18,19]. However, the distributions of maternal age and gestational age at NIPT, and the percentages of nulliparous and IVF-ET pregnancies were similar between the two groups of pregnant women with the dichotomous fetal fraction.…”
Section: Plos Onesupporting
confidence: 74%
“…This study is the first meta-analysis that evaluates factors affecting the reduction of FF ratios to less than 4% in the mother's blood. Factors that could alter the FF ratio are generally divided into three categories: maternal, fetal-placental, and experimental [23].…”
Section: Discussionmentioning
confidence: 99%